2019
DOI: 10.3390/su11102751
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Entrepreneurial Intentions of Science and Engineering Students in China: A Q Methodology Study

Abstract: The entrepreneurial intentions of Chinese students have received rapidly evolving attention, with the “mass entrepreneurship and innovation” program as a driving force, which encourages individuals to start their own business. Entrepreneurial intention, which is perceived as being a predictor of entrepreneurial behavior, has generally been explored in the existing literature on the basis of the theory of planned behavior and the intention–behavior model. Since intention is a psychological notion, it is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…Synthesizing this fast-growing body of empirical research and reviews on entrepreneurship education suggests two main patterns. First, a large number of studies on the impact of entrepreneurship education have focused on entrepreneurial attitudes and intentions ( Nabi et al, 2017 ), for instance, entrepreneurial intentions of business and engineering students ( Voda and Florea, 2019 ), entrepreneurial intentions of science and engineering students in China ( Fang and Chen, 2019 ), and internship quality on entrepreneurial intentions ( Yi, 2018 ). Second, few reviews focus on entrepreneurship education satisfaction of teachers and students specifically in higher education for sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Synthesizing this fast-growing body of empirical research and reviews on entrepreneurship education suggests two main patterns. First, a large number of studies on the impact of entrepreneurship education have focused on entrepreneurial attitudes and intentions ( Nabi et al, 2017 ), for instance, entrepreneurial intentions of business and engineering students ( Voda and Florea, 2019 ), entrepreneurial intentions of science and engineering students in China ( Fang and Chen, 2019 ), and internship quality on entrepreneurial intentions ( Yi, 2018 ). Second, few reviews focus on entrepreneurship education satisfaction of teachers and students specifically in higher education for sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Wach and Wojciechowski [11] reported that attitude, subjective norms, and perceived behavioural control determine the entrepreneurial intentions of students in Poland. Among Chinese engineering students, Fang and Chen [12] suggested that a subjective approach to entrepreneurship education can enrich entrepreneurial intentions. In Romania, a study conducted by Voda and Florea [13] reported that the locus of control, need for achievement, and entrepreneurial education are the key determinants for entrepreneurial intention among university students.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable literature on the impact of entrepreneurship on students. Fang and Chen (2019) explored the entrepreneurial intentions of science and engineering students in China. Pauceanu et al (2019) explored what determinants influence students to start their own business in United Arab Emirates Universities.…”
Section: Research On the Factors Linked To Teachers' Competencies In Eementioning
confidence: 99%